Multimodal suppression of vibration in smart flexible beam using piezoelectric electrode-based switching control - Lin, Chi-Ying; Huang, Yu-Hsi; Chen, Wei-Ting (Mechatronics (Oxford), 2018)
This paper describes an active vibration control system combining a piezoelectric electrode configured with a novel switching control system to achieve multimodal vibration suppression in smart flexible structures embedded with only a single piezoelectric actuator. The fact that high-frequency vibrations attenuate more rapidly than do low frequency vibrations motivated the development of a novel scheme in which the resonant excitation of coupled bending and lateral vibrations is applied to a cantilever beam. Switching times are determined using time-frequency analysis of modal responses. A smoothing function was applied to alleviate the effects of high-frequency oscillations during the switching control transition in order to facilitate the suppression of bending mode vibrations. Algorithms for proportional derivative (PD) control and positive position feedback (PPF) control can be tailored specifically for the target vibration modes and implemented in a variety of switching control schemes. The vibration responses induced by various switching control schemes was analyzed in order to derive appropriate control parameters for the development of an efficient switching control system aimed at suppressing multimodal vibrations. Experiment results demonstrate the effectiveness of the proposed piezoelectric electrode configuration in suppressing lateral mode vibrations. The proposed switching control system also proved highly satisfactory in suppressing vibrations in a system subject to simultaneous bending mode excitation.